Aplicação do processo de pirólise para valoração, cogeração de energia e tratamento de resíduos - Artur Tôrres Filho (2014)
Pyrolysis process is characterized as the thermal degradation of organic matter in an atmosphere with absence or deficiency of oxygen. Looking for solutions for waste treatment, the Federal University of Minas Gerais UFMG developed a research project in partnership with private institutions to study the application of the pyrolysis process in wastes, which resulted in a patent of the technology called pyrolix process. This work is composed of three chapters applying waste thermal treatment by pyrolysis to valuation, electricity cogeneration and waste treatment. At first, a study of the final product from pyrolysis of leather waste tanned with chromium is presented. The study of potential application of the carbonized leather waste (RCC) in metallurgical processes for production of iron ore pellets was investigated, and the results demonstrated technological feasibility of the application of the product as an energy source, with chromium recovery up to 76,47% in the iron ore pellets production tests. The pellets produced with replacement of 25% of the carbon contained in the mineral coal resulted in a mean value of 344 kgf.pellet-1 in the compression resistance tests against 300kgf.pellet-1 in the standard pellets. In another chapter, an assessment of the electricity generating potential in the treatment of MSW in two different conditions is presented. In the first situation, the carbonized municipal waste (RUC) is used as energy source, providing 34% of the plant electricity demand, in an integrated setting of a pyrolysis plant and an Organic Rankine Cicle (ORC) module, used for the electricity generation. In the second situation the carbonized product is used to generate electricity in a thermoelectrical plant located in a different site, in replacement to the traditional fuels. Applying this route in all Minas Geraiss cities under 30.000 inhabitants has demonstrated potential to supply a thermoelectrical plant with nominal capacity of 111 MW. At last, the technical and environmental evaluation of the pyrolysis treatment health waste is presented. The carbonized health waste (RSC) was characterized as class IIA waste not inert, in Brazilian standards. The greatest results regarding environmental safety were obtained in the third tested operation condition, concerning atmospheric emissions of pollutants, and the concentration of dioxins and furans obtained was 0,0162 ng.Nm-³. The studies have shown great potential for pyrolysis application in industrial and in MSW management - including health waste - contributing to the advancement of scientific knowledge of heat treatment process application.